Implementasi Program Keluarga Harapan (PKH) dalam Meningkatkan Kesejahteraan Masyarakat di Kabupaten Tabanan (Studi Kasus di Kecamatan Tabanan) - Diputra, I Kadek Dwi Rizky; Wijaya, Komang Adi Sastra; Wirantari, I Dewa Ayu Putri (Lenggogeni Data Publishing, 2025)
This research aims to analyze the implementation of the Family Hope Program (PKH) in Tabanan Regency (Case Study in Tabanan District) using Charles O. Jones' policy implementation theory, which includes indicators of organization, interpretation, and application. A qualitative research method with a descriptive approach was employed to allow for in-depth exploration of the phenomena in the field. Data collection was carried out through observation, in-depth interviews with the Secretary of the Social Affairs and Women's and Children's Empowerment Office (Dinas Sosial P3A) of Tabanan Regency, PKH facilitators in Tabanan District, and Beneficiary Families, as well as documentation studies. The research results indicate that the PKH implementing organization has a solid and responsive structure with active coordination. Interpretation regarding the program's objectives, mechanisms, and aid amounts is well understood through regular socialization and routine meetings. The application of PKH funds is appropriately utilized for nutrition and education, supported by continuous and persuasive oversight and assistance mechanisms. The study concludes that PKH's success in Tabanan is supported by systematic implementation, institutional clarity, consistent information dissemination, and active assistance. Therefore, the researchers recommend the replication of a similar model with local context adaptation and continuous improvements in aspects of facilitator capacity, village government involvement, fund disbursement access, transparency, and data integration to enhance program effectiveness. Abstrak Penelitian ini bertujuan menganalisis implementasi Program Keluarga Harapan (PKH) di Kabupaten Tabanan (Studi Kasus di Kecamatan Tabanan) menggunakan teori implementasi kebijakan Charles O. Jones, yang meliputi indikator organisasi, interpretasi, dan aplikasi. Metode penelitian kualitatif dengan pendekatan deskriptif memungkinkan ekplorasi mendalam terhadap fenomena di lapangan. Pengumpulan data dilakukan melalui observasi, wawancara mendalam dengan Sekretaris Dinas Sosial P3A Kabupaten Tabanan, pendamping PKH Kecamatan Tabanan, dan Keluarga Penerima Manfaat, serta studi dokumentasi. Hasil temuan menunjukkan bahwa organisasi pelaksana PKH memiliki struktur yang solid dan responsif dengan koordinasi aktif. Interpretasi terkait tujuan, mekanisme, dan besaran bantuan dipahami baik melalui sosialisasi dan pertemuan rutin. Aplikasi dana PKH dimanfaatkan secara tepat untuk gizi dan pendidikan, didukung mekanisme pengawasan dan pendampingan berkelanjutan yang persuasif. Simpulan penelitian mengonfirmasi keberhasilan PKH di Tabanan ditopang implementasi sistematis, kejelasan kelembagaan, diseminasi informasi konsisten, dan pendampingan aktif. Oleh karena itu, peneliti merekomendasikan perlunya replikasi model serupa dengan adaptasi konteks lokal dan perbaikan berkelanjutan pada aspek kapasitas pendamping, pelibatan pemerintah desa, akses pencairan dana, transparansi, serta integrasi data untuk peningkatan efektivitas program. Kata Kunci: PKH, Implementasi Kebijakan, Charles O Jones, Bantuan Bersyarat, Tabanan